TEACHING MATERIAL ON MOBILE LEARNING-BASED DIGITAL LITERACY AS A PREVENTIVE MEASURE FOR SOCIAL MEDIA CONFLICT - Ida Zulaeha; Lispridona Diner; Suratno Suratno; Cahyo Hasanudin; Areni Yulitawati Supriyono (Universitas Negeri Makassar, 2024)
This research was conducted with the aim of producing instructional materials on mobile learning-based digital literacy skills as a preventive measure for social media conflicts. The researchers conducted this study using a research and development (R&D) design. We conduct data collection through the techniques of observation, interview, and validation testing. Researchers use the qualitative analysis method to analyze data on instructional needs and validation. Based on the analysis of the collected data, researchers are able to draw conclusions. Media experts and subject matter experts present prominent findings and corrections, from which conclusions are derived. that the instructional materials on digital literacy based on mobile learning are suitable for use as a preventive measure for social media conflicts.